On n-fold fuzzy positive implicative ideals of BCK-algebras - Young Bae Jun; Kyung Ho Kim (International Journal of Mathematics and Mathematical Sciences)
We consider the fuzzification of the notion of an n-fold positive implicative ideal. We give characterizations of an n-fold fuzzy positive implicative ideal. We establish the extension property for n-fold fuzzy positive implicative ideals, and state a characterization of PIn-Noetherian BCK-algebras. Finally we study the normalization of n-fold fuzzy positive implicative ideals.